2002
DOI: 10.1016/s0896-6273(02)00699-2
|View full text |Cite
|
Sign up to set email alerts
|

A Presynaptic Kainate Receptor Is Involved in Regulating the Dynamic Properties of Thalamocortical Synapses during Development

Abstract: Previous studies have shown that pharmacological activation of presynaptic kainate receptors at glutamatergic synapses facilitates or depresses transmission in a dose-dependent manner. However, the only synaptically activated kainate autoreceptor described to date is facilitatory. Here, we describe a kainate autoreceptor that depresses synaptic transmission. This autoreceptor is present at developing thalamocortical synapses in the barrel cortex, specifically regulates transmission at frequencies corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 53 publications
5
57
0
2
Order By: Relevance
“…Synaptically released glutamate, acting on kainate receptors, has been shown to modulate excitatory transmission in the hippocampus (Contractor et al, 2001;Lauri et al, 2001) and immature neocortex (Kidd and Issac, 2001;Kidd et al, 2002). In the present study we found that bath application of the GluR5 antagonist LY382884 decreased EPSC amplitudes and changed paired-pulse facilitation to paired-pulse depression.…”
Section: Kainate Facilitation Involves Glur5 Subunitssupporting
confidence: 58%
See 2 more Smart Citations
“…Synaptically released glutamate, acting on kainate receptors, has been shown to modulate excitatory transmission in the hippocampus (Contractor et al, 2001;Lauri et al, 2001) and immature neocortex (Kidd and Issac, 2001;Kidd et al, 2002). In the present study we found that bath application of the GluR5 antagonist LY382884 decreased EPSC amplitudes and changed paired-pulse facilitation to paired-pulse depression.…”
Section: Kainate Facilitation Involves Glur5 Subunitssupporting
confidence: 58%
“…Physiologically released glutamate has been shown to modulate excitatory transmission in the hippocampus (Contractor et al, 2001;Lauri et al, 2001) and immature neocortex (Kidd and Issac, 2001;Kidd et al, 2002). To test whether synaptically released glutamate could affect EPSCs in layer II/III pyramidal cells, we examined responses to paired pulse stimulation before and after bath application of the GluR5 antagonist LY382884.…”
Section: Facilitation Of Spontaneous Epscs By Kainatementioning
confidence: 99%
See 1 more Smart Citation
“…A large number of genes, potentially involved in synaptic plasticity and axon growth, have been found to be transiently expressed in the ventrobasal thalamic nuclei, with a time course that could match the time course of this form of TCA plasticity because they are maximal during the first postnatal week, with a rapid decrease of expression after P10. Among these genes, the kainate receptors (Kidd et al, 2002), adenylate cyclase 1 (Nicol et al, 2005), the serotonin transporter, and the 5-HT 1B receptor (for review, see Gaspar et al, 2003) could potentially be important for permitting this developmental remodeling of thalamocortical axons to occur.…”
Section: Discussionmentioning
confidence: 99%
“…This developmental decrease closely matches the developmental loss of the ability to induce LTP at these synapses (Crair and Malenka, 1995) supporting the idea that unsilencing is an important mechanism for TC LTP. Subsequent evidence for the presence of silent TC synapses has come in the form of differing short-term plasticity of AMPA and NMDA receptor-mediated synaptic currents (Yanagisawa et al, 2004) although these data appear to contradict finding of other groups at the same synapse (Gil et al, 1997;Gil et al, 1999;Kidd et al, 2002).…”
Section: Long-term Potentiation (Ltp) At Tc Synapsesmentioning
confidence: 97%